Indiana university (Trustees of Indiana University, 1999)
Thinking of attending Indiana University? This Web site will help you learn all about what IU has to offer--enabling you to decide if it may be the right school for you. This university excels in fine arts, social work, business, education, journalism, nursing, and optometry. Come read up-to-date IU news, learn about undergraduate and graduate programs offered, explore student life, and much more!